An Antecedents and Outcomes of Service Recovery Performance, The Case of Hospitality Industry in North Cyprus - Mosavat, Nikoo (Eastern Mediterranean University EMU, 2015)
The main aim of this study is to identify factors affecting service recovery performance and its outcomes in the case of five-star hotels in North Cyprus. The total number of 214 frontline employees participated in this study. Accordingly, judgmental sampling that is a type of non-probability sampling has been applied for collecting data. This study suggested a conceptual model that tested the impact of managerial attitudes and frontline staffs’ perceptions of their work environment influence Service Recovery performance. More specifically, the study tests the impact of managerial attitudes and frontline staffs’ perceptions of their work environment on service recovery performance and the effect on service recovery performance on employees’ intentions to resign and their job satisfaction. These relations have been tested referring to social exchange theory. The association of these constructs was tested by using SPSS 20. The results clearly demonstrated that several factors impacts Service Recovery performance in hotels in North Cyprus which consequently affect employee intentions to resign and their job satisfaction. The results emerging from the current study proposed useful implications for managers and hotel owners in North Cyprus. Additionally, some information regarding the limitations of this study as well as implication for future inquiry was presented in this thesis. Keywords: service recovery performance, managerial attitude, intentions to resign, job satisfaction

ӦZ: Bu çalışmanın temel amacı, hizmet iyileştirme performansını etkileyen faktörler ve bunların Kuzey Kıbrıs’taki beş yıldızlı otellerdeki sonuçlarını etkileyen faktörleri tespit etmektir. 214 sınır birim çalışanı çalışmaya katılmıştır. Bu çalışmada kavramsal model test edilmiş ve yönetsel tutum ile sınır birim çalışanlarının çalışma koşullarının hizmet iyileştirme performansına etkileri ortaya konmaya çalışılmıştır. İlişkiler SPSS 20 ile test edilmiş ve Kuzey Kıbrıs’taki beş yıldızlı otellerdeki sınır birim çalışanlarının hizmet iyileştirme performansının işten ayrılmaya niyetli olma ve iş tatminleri üzerinde etkili olduğu sonucuna varılmıştır. Bu çalışmanın bir diğer sonucu da, bulguların Kuzey Kıbrıs'taki otel yöneticileri ile otel sahiplerine sağlayacağı faydalar olmuştur. Ayrıca, çalışma esnasında karşılaşılan kısıtlamaların etkisinin sonraki çalışmalara ışık tutacağı bilgisi de Çalışmada belirtilmiştir. Anahtar kelimeler: hizmet iyileştirme performansı, yönetimsel davranış, işten ayrılmaya niyetli olma ve iş tatmini.
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2015. Supervisor: Assist. Prof. Dr. Güven M. Ardahan.
Keywords: Tourism; Tourism-Iran; North; Service Quality and Performance-Management-Tourism and Hospitality Industry-Cyprus; Service recovery performance; managerial attitude; intentions to resign; job satisfaction